2021
DOI: 10.3126/jcmsn.v17i2.30499
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of life of Diabetic and Non-Diabetic Elderly in a Municipality of Central Nepal

Abstract: Background: Quality of life (QoL) is the perception of an individual about their position in life. Chronic diseases such as diabetes are said to have influence on QoL. Health condition changes with increased age and chronic disease condition. This study aimed to assess Health-Related QoL of diabetic and non-diabetic elderly. Method: A community based cross-sectional study was conducted among 167 elderly in Gaindakot municipality of Nawalpur, Nepal. Health related QoL was assessed using World Health Organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
2
0
0
1
Order By: Relevance
“…In terms of religion, 73% of male and 71.8% of female elderly fallowed Hinduism fallowed by 45.1% of male and 46.3% of female elderly from Brahmin/ Chhetri ethnic group. Moreover, this study finding was supported by studies conducted in Morang, Nepal (Shrestha et al, 2018) and Northern India (Sapkota et al, 2021) found that, 90% of respondents followed Hinduism. While, 55% of respondents were from Brahmin/Chettri ethnic group (Shrestha et al, 2018)as well as a study held in central Nepal (Sapkota et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In terms of religion, 73% of male and 71.8% of female elderly fallowed Hinduism fallowed by 45.1% of male and 46.3% of female elderly from Brahmin/ Chhetri ethnic group. Moreover, this study finding was supported by studies conducted in Morang, Nepal (Shrestha et al, 2018) and Northern India (Sapkota et al, 2021) found that, 90% of respondents followed Hinduism. While, 55% of respondents were from Brahmin/Chettri ethnic group (Shrestha et al, 2018)as well as a study held in central Nepal (Sapkota et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, this study finding was supported by studies conducted in Morang, Nepal (Shrestha et al, 2018) and Northern India (Sapkota et al, 2021) found that, 90% of respondents followed Hinduism. While, 55% of respondents were from Brahmin/Chettri ethnic group (Shrestha et al, 2018)as well as a study held in central Nepal (Sapkota et al, 2021). This study also found that more than fifty percent of both male and female elderly were suffering from any type of chronic disease especially high blood pressure among both male (65.7%) and female (50.9%) elderly.…”
Section: Discussionsupporting
confidence: 80%
“…Domain kesehatan fisik meliputi aktivitas kehidupan sehari-hari, ketergantungan pada kandungan obat dan alat bantu medis, energi dan kelelahan, mobilitas, rasa sakit (nyeri) dan ketidaknyamanan, tidur dan istirahat dan kapasitas kerja (Sapkota et al, 2021). Skor kualitas hidup yang rendah pada domain fisik menunjukkan rendahnya kapasitas kerja, meningkatnya ketergantungan pada obat-obatan dan kelelahan serta berkurangnya mobilitas dalam kehidupan sehari-hari (Sahoo et al, 2023).…”
Section: Pembahasanunclassified